Portrait of Chemistry Teachers' Readiness in Implementing the Independent Curriculum in High Schools - Suciana, Dola; Fahimah Diniyah Wathi, Ayu; Sausan, Inas; Akhmad Adi Masbukhin, Faizal; Lisa Rosanna, Desi (Chemistry Education Department of Education and Teaching Faculty, 2024)
This research aims to describe portrait of chemistry teachers' readiness to implement the Independent Curriculum in high schools throughout South Tangerang City. The Independent Curriculum aims to increase the relevance and quality of education in Indonesia. The research was conducted using a quantitative approach with descriptive data analysis. This research was conducted in South Tangerang City involving 56 chemistry teachers at high schools in South Tangerang City. The type of data used in this research is primary data. The instrument used to collect data in this research was a list of questions in the form of a questionnaire. The results of the research show that chemistry teachers in South Tangerang City are relatively ready to implement the independent curriculum in the schools where they teach. Researchers looked at the level of teacher readiness in implementing the independent curriculum from their knowledge regarding the characteristics and structure of the independent curriculum, readiness in planning learning, readiness in implementing learning, and readiness in implementing learning assessments. This research provides insight into the development of educational policies and the development of teacher professionalism in facing the challenges of the new curriculum.